Multiparity, Brain Atrophy, and Cognitive Decline - Jung, Joon Hyung; Lee, Ga Won; Lee, Jun Ho; Byun, Min Soo; Yi, Dahyun; Jeon, So Yeon; Jung, Gi Jung; Joung, Haejung; Shin, Seong A; Kim, Yu Kyeong; Kang, Koung Mi; Sohn, Chul-Ho; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Multiparity—grand multiparity (i.e., five or more childbirths) in particular—has been reported to have an association with increased risk of Alzheimer’s disease (AD) dementia or related cognitive decline in women. However, the pathological links underlying this relationship are still unknown. This study was conducted to examine the relationships of multiparity with cerebral amyloid-beta (Aβ) deposition, brain atrophy, and white matter hyperintensities (WMHs). Methods: In this study, total of 237 older women with 148 cognitively normal and 89 mild cognitive impairment from the Korean Brain Aging Study for Early Diagnosis and Prediction of Alzheimer’s Disease (KBASE) were included. Participants underwent clinical and neuropsychological assessments in addition to 11C-labeled Pittsburgh Compound B positron emission tomography, and magnetic resonance imaging. The associations of parity with Aβ deposition, hippocampal volume, cortical volume, WMH volume and mini-mental status examination (MMSE) score were examined. Results: Participants with grand multiparity showed significantly reduced adjusted hippocampal volume, spatial pattern of atrophy for recognition of AD volume and spatial pattern of atrophy for recognition of brain aging volume even after controlling for potential confounders. Furthermore, MMSE score was also significantly lower in this group. In contrast, grand multiparity did not show any association with global Aβ retention, Aβ positivity rate, or WMH volume, regardless of covariates. Conclusions: Our findings suggest that grand multiparity contributes to cognitive decline or increased dementia risk in older women by aggravating amyloid-independent hippocampal or cortical atrophy.